2018
DOI: 10.1016/j.ajme.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Plasma soluble CD 163 level as a marker of oesophageal varices in cirrhotic patients

Abstract: Background: Variceal bleeding (VB), the most common lethal complication of cirrhosis, associated with high mortality. Timely prediction of esophageal varices (EV) represents a real challenge for the medical team. This study evaluated the level of plasma soluble CD 163 as a marker of the presence of EVs and to compare it with other noninvasive clinical, laboratory and ultrasonographic parameters as well as endoscopy. Methods: This prospective controlled study was conducted on 80 adults. Gp I had no oesophageal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 51 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Agha et al [54] identified a PSR of 792 as the best cutoff value for the presence of EV in patients with compensated HCV-related cirrhosis and suggested that a greater ratio could be useful to identify patients at low risk of having EV on endoscopic surveillance. A modestly lower cutoff value was reported in other studies yielding good sensitivities and specificities for prediction of EV in cirrhotic patients, but it did not appear to predict the grade of varices [35, 55]. Excitingly, an Egyptian study used a cut-off value of 1,326.58 for the PSR to predict EV in HCV-related cirrhosis at 96.34% sensitivity and 94% diagnostic accuracy [56].…”
Section: Discussion/conclusionmentioning
confidence: 94%
See 3 more Smart Citations
“…Agha et al [54] identified a PSR of 792 as the best cutoff value for the presence of EV in patients with compensated HCV-related cirrhosis and suggested that a greater ratio could be useful to identify patients at low risk of having EV on endoscopic surveillance. A modestly lower cutoff value was reported in other studies yielding good sensitivities and specificities for prediction of EV in cirrhotic patients, but it did not appear to predict the grade of varices [35, 55]. Excitingly, an Egyptian study used a cut-off value of 1,326.58 for the PSR to predict EV in HCV-related cirrhosis at 96.34% sensitivity and 94% diagnostic accuracy [56].…”
Section: Discussion/conclusionmentioning
confidence: 94%
“…An Egyptian study found that the mean serum sCD163 level in cirrhotic patients with and without EV was increased fairly 3 times more than that of the control group and nearly doubled in patients with EV than patients without varices ( p = 0.001); hence, it could potentially predict the presence of EV in Child-Pugh class A cirrhotic patients [34]. Another study found that serum sCD163 is a good noninvasive predictor for the presence of EV and may be used to determine the grade of varices [35]. It showed that the median serum sCD163 concentration was significantly elevated in cirrhotic patients with and without EV compared to healthy subjects ( p = 0.009) and significantly higher in patients with large-size EV compared to patients with small-size varices ( p < 0.001).…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations